Pengaruh Pendapatan Asli Daerah, Pendapatan Transfer dan Pertumbuhan Ekonomi Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota Di Provinsi Jawa Tengah - Fajar Syaiful Akbar; Fariz Isyraqi Aryasandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Utilizing data collected from 2018 to 2022, this research will analyze the influence of local original income, transfer income and economic growth of Regency/City Regional Governments in Central Java Province. The object of this research is the Regency/City Regional Government of Central Java Province. This research data was compiled using statistical information on Gross Regional Domestic Product (GRDP) and reports on the realization of the APBD budget of Regency/City Regional Governments in Central Java Province. This type of research is quantitative research. The sampling method used was purposive sampling with a total of 33 Regency/City local governments selected as samples. Secondary sources, such as papers released by the official DJPK website of the Ministry of Finance and the Central Statistics Agency, were the data sources used in this research. Research data were analyzed using multiple linear regression. Regional original income, transfer income and economic growth are three factors that influence the performance of district and city government budgets in Central Java Province, according to the research. This study finds that although local revenue has a negative influence and transfer income has a positive influence on the financial performance of the regional government of Central Java Province, economic growth has the opposite impact.